2008
DOI: 10.2174/138920008784746391
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Clinical Drug Interactions with the Herbal Antidepressant St. Johns wort

Abstract: St. John's wort (Hypericum perforatum, SJW) is one of the most commonly used herbal antidepressants for the treatment of minor to moderate depression. Limited clinical trials suggest that hypericum and standard antidepressants have similar beneficial effects, but current evidence regarding the antidepression effects of SJW extracts is inconsistent. A major safety concern about SJW is its ability to alter the pharmacokinetics and/or clinical response of a variety of clinically important drugs. This review highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 128 publications
(170 reference statements)
0
41
0
5
Order By: Relevance
“…Since then there are frequent reports of pharmacokinetic interactions of herbs with drugs, causing either beneficial or harmful effects (44,53). Combined use of herbs with drugs may mimic, increase, or reduce the effects of either component, resulting in herb-drug interactions (60). The herb-drug interactions can be hazardous if they cause increased drug levels reaching above toxic threshold.…”
Section: Herbal Modulation Of P-gpmentioning
confidence: 99%
“…Since then there are frequent reports of pharmacokinetic interactions of herbs with drugs, causing either beneficial or harmful effects (44,53). Combined use of herbs with drugs may mimic, increase, or reduce the effects of either component, resulting in herb-drug interactions (60). The herb-drug interactions can be hazardous if they cause increased drug levels reaching above toxic threshold.…”
Section: Herbal Modulation Of P-gpmentioning
confidence: 99%
“…In contrast, the measurement of liver weight was simple and the increased ratio of liver weight to body weight corresponded well to the induction of CYP by CFE (22); the correlation coefficient was 0.85 (n535, p,0.001). When the relationship between hepatic CYP content and liver weight to body weight was reanalyzed using the data from the CFE dose-response study (17), a significant positive correlation was also detected (r50.78, n526, p,0.001). Thus, we used the increase in the ratio of liver weight to body weight as a simple and reliable indicator of CYP induction following CFE treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs are metabolized by the Phase I and Phase II enzymes; the former is catalyzed by cytochrome P450 (CYP) enzymes, and the latter is catalyzed conjugation enzymes such as glutathione S-transferase (GST) and UDP-glucuronosyltransferase (16). Interactions between some herbal ingredients, such as St John's wort (17) and ginkgo biloba (18), have been documented and shown to be mediated by CYPs, but those for other herbal ingredients remain unknown. We previously showed that feeding mice a diet containing CFE (standardized with 10% forskolin) dose-and time-dependently induced hepatic CYPs and GST enzymes (19).…”
mentioning
confidence: 99%
“…Although herbs may well have undesirable side effects, there are no set "doses," and herb-drug or herb-herb interactions are possible. Several researches in this aspect are available from number of clinicians which provides the proof of herb-herb and herb-drug interactions in both positive and negative directions (Chavez et al, 2006;Iqbal et al, 2015;Shu, 1998;Thomas et al, 2004;Zhou et al, 2008). A major hypothetical advantage of botanicals over conventional single-component drugs is the presence of multiple active compounds that together can provide a potentiating effect that may not be achievable by any single compound.…”
Section: Threats and Challengesmentioning
confidence: 99%